Techno-Economic Assessment of Active Latent Heat Thermal Energy Storage Systems with Low-Temperature District Heating - Castro Flores, Jose Fiacro; Rossi Espagnet, Alberto; Chiu, Justin NingWei; Martin, Viktoria; Lacarrière, Bruno (International Journal of Sustainable Energy Planning and Management, 2017)
Thermal energy storage (TES) is a set of technologies with the potential to enhance the efficiency and flexibility of the 4th generation of district heating systems. This study presents a comparative techno-economic assessment of active TES systems suited to operate with low-temperature district heating (LTDH) for short-term heat storage applications. Latent heat systems (LH-TES) are compared qualitatively and quantitatively to water-based sensible heat systems (SH-TES). It is concluded that latent heat TES systems are still more expensive than water-based systems regarding energy storage cost (EUR/kWh) ranging from 1.5 to 4 times more, mainly due to the cost of the storage media. However, considering distributed TES systems integrated to LTDH, small-scale active LH-TES systems will become more cost-competitive as storage media costs are expected to decline in the future. This study represents a step forward in the development and improvement of the DH system through the integration of TES which will play a key role in the future smart energy system.